2023
DOI: 10.3390/futuretransp3020024
|View full text |Cite
|
Sign up to set email alerts
|

Last-Mile Logistics Network Design under E-Cargo Bikes

Abstract: E-cargo bikes, i.e., electric bicycles equipped with baskets for transporting goods, are perceived as an advantageous solution for urban last-mile logistics. Particularly for short distances and low volumes of goods, the use of e-cargo bikes is ideal in urban areas where access of conventional cars may be prohibited. In this context, this study presents an e-cargo bike routing model for urban deliveries. The problem is formulated as a Capacitated Vehicle Routing Problem (CVRP), which takes several aspects into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Further, a literature review [9] that related the factors within mobile applications that encourage sustainable choices found that a well-designed approach incorporating financial incentives and environmental consciousness could boost public transport usage. Alternatively, the shipping mode may include electric bicycles [10,11] as a solution for urban last-mile deliveries.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Further, a literature review [9] that related the factors within mobile applications that encourage sustainable choices found that a well-designed approach incorporating financial incentives and environmental consciousness could boost public transport usage. Alternatively, the shipping mode may include electric bicycles [10,11] as a solution for urban last-mile deliveries.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Where the entry of ICEVs is constrained or prohibited [92], and also in the case of the numerous spatial limitations found especially in city centres, cargo deliveries supporting energy transition may also be made using the vehicles categorised as light electric freight vehicles (LEFVs). According to Balm et al [93], LEFVs are electrically powered or electrically assisted vehicles that are smaller than a van and have a maximum loading capacity of 750 kg.…”
mentioning
confidence: 99%